2015
DOI: 10.1128/mcb.00102-15
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Pathway Effector YAP Regulates Motility, Invasion, and Castration-Resistant Growth of Prostate Cancer Cells

Abstract: f Yes-associated protein (YAP) is an effector of the Hippo tumor suppressor pathway. The functional significance of YAP in prostate cancer has remained elusive. In this study, we first show that enhanced expression of YAP is able to transform immortalized prostate epithelial cells and promote migration and invasion in both immortalized and cancerous prostate cells. We found that YAP mRNA was upregulated in androgen-insensitive prostate cancer cells (LNCaP-C81 and LNCaP-C4-2 cells) compared to the level in andr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
155
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(159 citation statements)
references
References 81 publications
(97 reference statements)
4
155
0
Order By: Relevance
“…In line with in vitro and murine-model results, YAP over-expression and/or nuclear accumulation has been detected in several human malignant tumors such as prostate, colorectal and lung cancer as well as HCC [4,[7][8][9][10][11][12]. In the latter, YAP expression also was also found to influence the prognosis and was associated with poorer tumor cell differentiation [13,14].…”
Section: Introductionsupporting
confidence: 53%
“…In line with in vitro and murine-model results, YAP over-expression and/or nuclear accumulation has been detected in several human malignant tumors such as prostate, colorectal and lung cancer as well as HCC [4,[7][8][9][10][11][12]. In the latter, YAP expression also was also found to influence the prognosis and was associated with poorer tumor cell differentiation [13,14].…”
Section: Introductionsupporting
confidence: 53%
“…Some of these proteins were reported to be related with AIPC. YAP was recently identified as a novel regulator of prostate cancer cell motility, invasion, and androgen independent growth [21,22] and was considered as a potential therapeutic target for metastatic AIPC. YAP1 is a transcriptional regulator which can act both as a co-activator and a co-repressor; it is a critical downstream regulatory target in the Hippo signaling pathway that plays a Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Its deregulation is frequently observed in many types of malignancies, suggesting that alterations of this signaling are connected with cancer progression and patient survival (7)(8)(9)21,33,34). The core components of this pathway include MST1/2, SAV1, LATS1/2 and MOB1 proteins (10,12,15).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…The reported associations between decreased levels of either miR-509-3p or miR-138 in the studied types of cancer and poorer patient outcome (63)(64)(65), consolidating the influence of YAP1 in tumor progression. In fact, the contribution of YAP1 protein in tumor progression is so important that it was acknowledged as a pivotal molecular target in modern cancer treatment (5,34,38,51,52,66,67). Some authors found an association between YAP1 overexpression and chemoresistance of cancer cells, e.g., in head and neck cancer cases resistant to cetuximab (57), resistance to RAF-and MEK-targeted therapy (33), 5-FU chemotherapy-resistant colon cancer (68) and osteosarcoma resistance (69).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%